Additional three patients with Smith‐McCort dysplasia due to novel RAB33B mutations. Issue 3 (27th January 2017) - Salian, Smrithi; Cho, Tae‐Joon; Phadke, Shubha R.; Gowrishankar, Kalpana; Bhavani, Gandham SriLakshmi; Shukla, Anju; Jagadeesh, Sujatha; Kim, Ok‐Hwa; Nishimura, Gen; Girisha, Katta M.
Abstract : Smith‐McCort dysplasia (SMC OMIM 615222) and Dyggve‐Melchior‐Clausen dysplasia (DMC OMIM 223800) are allelic skeletal dysplasias caused by homozygous or compound heterozygous mutations in DYM (OMIM 607461). Both disorders share the same skeletal phenotypes characterized by spondylo‐epi‐metaphyseal dysplasia with distinctive lacy ilia. The difference rests on the presence or absence of intellectual disability, that is, intellectual disability in DMC and normal cognition in SMC. However, genetic heterogeneity was suspected in SMC. Recently, RAB33B (OMIM 605950) has been identified as the second gene for SMC. Nevertheless, only two affected families have been reported so far. Here we present three SMC patients with four novel pathogenic variants in RAB33B, including homozygosity for c.211C>T (p.R71*), homozygosity for c.365T>C (p.F122S), and compound heterozygosity for c.48delCGGGGCAG (p.G17Vfs*58) and c.490C>T (p.Q164*). We also summarize the clinical, radiological, and mutation profile of RAB33B after literature mining. This report ascertains the pathogenic relationship between RAB33B and SMC. © 2017 Wiley Periodicals, Inc.